Gliomatosis cerebri: no evidence for a separate brain tumor entity - Herrlinger, Ulrich; Jones, David T. W.; Glas, Martin; Hattingen, Elke; Gramatzki, Dorothee; Stuplich, Moritz; Felsberg, Jörg; Bähr, Oliver; Gielen, Gerrit H.; Simon, Matthias; Wiewrodt, Dorothee; Schabet, Martin; et al. (Acta neuropathologica, 2016)
Gliomatosis cerebri (GC) is presently considered a distinct astrocytic glioma entity according to the WHO classification for CNS tumors. It is characterized by widespread, typically bilateral infiltration of the brain involving three or more lobes. Genetic studies of GC have to date been restricted to the analysis of individual glioma-associated genes, which revealed mutations in the isocitrate dehydrogenase 1 (IDH1) and tumor protein p53 (TP53) genes in subsets of patients. Here, we report on a genome-wide analysis of DNA methylation and copy number aberrations in 25 GC patients. Results were compared with those obtained for 105 patients with various types of conventional, i.e., non-GC gliomas including diffuse astrocytic gliomas, oligodendrogliomas and glioblastomas. In addition, we assessed the prognostic role of methylation profiles and recurrent DNA copy number aberrations in GC patients. Our data reveal that the methylation profiles in 23 of the 25 GC tumors corresponded to either IDH mutant astrocytoma (n = 6), IDH mutant and 1p/19q codeleted oligodendroglioma (n = 5), or IDH wild-type glioblastoma including various molecular subgroups, i.e., H3F3A-G34 mutant (n = 1), receptor tyrosine kinase 1 (RTK1, n = 4), receptor tyrosine kinase 2 (classic) (RTK2, n = 2) or mesenchymal (n = 5) glioblastoma groups. Two tumors showed methylation profiles of normal brain tissue due to low tumor cell content. While histological grading (WHO grade IV vs. WHO grade II and III) was not prognostic, the molecular classification as classic/RTK2 or mesenchymal glioblastoma was associated with worse overall survival. Multivariate Cox regression analysis revealed MGMT promoter methylation as a positive prognostic factor. Taken together, DNA-based large-scale molecular profiling indicates that GC comprises a genetically and epigenetically heterogeneous group of diffuse gliomas that carry DNA methylation and copy number profiles closely matching the common molecularly defined glioma entities. These data support the removal of GC as a distinct glioma entity in the upcoming revision of the WHO classification.
Published online: 22 October 2015
Gesehen am 13.05.2020